Influence of Fc gamma RIIIb polymorphism on its ability to cooperate with Fc gamma RIIa and CR3 in mediating the oxidative burst of human neutrophils - Urbaczek, Ana Carolina [UNESP]; Toller-Kawahisa, Juliana Escher; Fonseca, Luiz Marcos [UNESP]; Costa, Paulo Inácio da [UNESP]; Quinello Gomes Faria, Carolina Maria [UNESP]; Caleiro Seixas Azzolini, Ana Elisa; Lucisano-Valim, Yara Maria; Marzocchi-Machado, Cleni Mara (Elsevier B.V., 2014)
Considering that human neutrophil Fc gamma RIIa and Fc gamma RIIIb receptors interact synergistically with CR3 in triggering neutrophil functional responses, allelic polymorphisms in these receptors might influence such interactions. We assessed whether Fc gamma RIIIb polymorphisms affect Fc gamma R/CR cooperation in mediating the neutrophil oxidative burst (OB), in particular the Fc gamma RIIIb/CR3 cooperation that occurs via lectin-saccharide-like interactions. The OB of human neutrophil antigen (HNA)-1a-, HNA-1b-, and HNA-1a/-1b-neutrophils stimulated with immune complexes, opsonized or not with serum complement, was measured by the luminol-enhanced chemiluminescence assay. Compared with HNA-1a-neutrophils, HNA-1b-neutrophils exhibited reduced Fc gamma R-stimulated OB, but increased Fc gamma R/CR-stimulated OB. It suggests that (i) Fc gamma R and CR cooperate more effectively in HNA-1b-neutrophils, and (ii) the HNA-1b allotype influences the Fc gamma RIIIb cooperation with Fc gamma RIIa, but not with CR3. HNA-1a- and HNA-1b-neutrophils exhibited similar OB responses elicited via CR3 alone or via Fc gamma R/CR-independent pathways. In addition, the level of Fc gamma RIIIb, Fc gamma RIIa, and CR3 expression did not differ significantly among the neutrophil groups studied. Together, these results demonstrate that the HNA-1b allotype influences the functional cooperation between Fc gamma RIIIb and Fc gamma RIIa, and suggest that the difference in the glycosylation pattern between HNA-1a and HNA-1b does not affect the Fc gamma RIIIb cooperation with CR3. (C) 2014 American Society for Histocompatibility and Immunogenetics. Published by Elsevier Inc. All rights reserved.
Keywords: Fc gamma receptor; Polymorphism; Neutrophil; Oxidative burst; Complement receptor